Rancang Bangun Solar Water Heater Dengan Kolektor Pelat Datar Berbentuk Spiral Berbasis Mikrokontroler - Ocsirendi Ocsirendi; Indra Dwisaputra; M Yunuf; Irfan Rahmi (Politeknik Manufaktur Negeri Bangka Belitung, 2018)
Bangka Island has high sunlight intensity, but it still has little use as an alternative energy source. Water heater available on the market have experienced a peak of innovation that continues to use electricity as energy, but as we know that heater that use electricity consume a lot of energy. In this research, a solar water heater machine with spiral collector will be made to heat water in a reservoir using sunlight energy and as a tool to see the difference between the continuous method which circulates water continuously from the reservoir to the heat collector with a delay method that circulates water with a certain delay time. Both methods and data retrieval mechanisms are controlled by an Arduino device. Based on the results of the trial, it was found that Solar water heater was able to heat water in reservoir up to 48.92 degrees Celsius and the use of the continuous method made the water temperature higher than the delay method with a maximum difference of 10.66 degrees centigrade.